2020
DOI: 10.1534/genetics.119.302973
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Involvement of Spliceosomal Mutations in Myelodysplastic Disorders from Analysis of SACY-1/DDX41 inCaenorhabditis elegans

Abstract: Mutations affecting spliceosomal proteins are frequently found in hematological malignancies, including myelodysplastic syndromes and acute myeloid leukemia (AML). DDX41/Abstrakt is a metazoan-specific spliceosomal DEAD-box RNA helicase that is recurrently mutated in inherited myelodysplastic syndromes and in relapsing cases of AML. The genetic properties and genomic impacts of disease-causing missense mutations in DDX41 and other spliceosomal proteins have been uncertain. Here, we conduct a comprehensive anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 97 publications
2
36
2
Order By: Relevance
“…While our RNASeq data showed that DDX41 had the greatest effects on transcript levels in LSK+ cells, the data also showed that DDX41 loss altered exon skipping and intron retention. In contrast to our results, in HeLa cells A3SS, A5SS and SE were all regulated by DDX41, while in C. elegans upon gene deletion, A3SS represented the predominant splicing defect (26,27). Whether these differences are species-or cell type-specific remains to be determined.…”
Section: Discussioncontrasting
confidence: 99%
“…While our RNASeq data showed that DDX41 had the greatest effects on transcript levels in LSK+ cells, the data also showed that DDX41 loss altered exon skipping and intron retention. In contrast to our results, in HeLa cells A3SS, A5SS and SE were all regulated by DDX41, while in C. elegans upon gene deletion, A3SS represented the predominant splicing defect (26,27). Whether these differences are species-or cell type-specific remains to be determined.…”
Section: Discussioncontrasting
confidence: 99%
“…OOC-5::GFP::TEV::3×FLAG and interacting proteins were purified from soluble protein extracts and membrane protein fractions prepared from the DG4377 strain using modifications of methods we previously described ( 47 49 ) as detailed in SI Appendix . Purifications from the wild-type strain (N2) were run in parallel as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Lanes were subdivided into six slices and mass spectrometry was performed at the Taplin Biological Mass Spectrometry Facility (Harvard Medical School) using an LTQ ion-trap mass spectrometer. In addition to control immunopurifications from the N2 strain, to account for abundant contaminant proteins that bound nonspecifically to the immunopurification matrix, we utilized data from multiple purifications of GFP fusion proteins, which we previously reported ( 47 49 ; see SI Appendix , Materials and Methods for the details of the filtering criteria used).…”
Section: Methodsmentioning
confidence: 99%
“…Dead box helicase (DDX41) is a tumor suppressor that is conserved in D.melanogaster, C.elegans, D.rerio and plants, and is considered essential to cell growth and viability [32][33][34][35] .…”
mentioning
confidence: 99%
“…DDX41 has been reported to interact with components of the spliceosome, and DDX41 deletion or mutations led to splicing defects and faulty RNA processing 38 . The role of DDX41 in RNA processing appears to be conserved: The C.elegans orthologue SACY-1 was recently shown to associate with the spliceosome, and impacts the transcriptome through splicing-dependent and -independent mechanisms 33 . Despite the relevance of DDX41 in cancer, the cellular and molecular functions of DDX41 remain poorly understood.…”
mentioning
confidence: 99%